Noradrenergic Source of Dopamine Assessed by Microdialysis in the Medial Prefrontal Cortex - Devoto, Paola; Sagheddu, Claudia; Santoni, Michele; Flore, Giovanna; Saba, Pierluigi; Pistis, Marco; Gessa, Gian Luigi (Frontiers in Pharmacology, 2020)
Previous results indicate that dopamine (DA) release in the medial prefrontal cortex (mPFC) is modified by 2 adrenoceptor- but not D2 DA receptor- agonists and antagonists, suggesting that DA measured by microdialysis in the mPFC originates from noradrenergic terminals. Accordingly, noradrenergic denervation was found to prevent 2-receptor-mediated rise and fall of extracellular DA induced by atipamezole and clonidine, respectively, in the mPFC. The present study was aimed to determine whether DA released by dopaminergic terminals in the mPFC is not detected by in vivo microdialysis because is readily taken up by norepinephrine transporter (NET). Accordingly, the D2-antagonist raclopride increased the electrical activity of DA neurons in the ventral tegmental area (VTA) and enhanced extracellular DOPAC but failed to modify DA in the mPFC. However, in rats whose NET was either inactivated by nisoxetine or eliminated by noradrenergic denervation, raclopride still elevated extracellular DOPAC and activated dopaminergic activity, but also increased DA. Conversely, the D2-receptor agonist quinpirole reduced DOPAC but failed to modify DA in the mPFC in control rats. However, in rats whose NET was eliminated by noradrenergic denervation or inhibited by locally perfused nisoxetine, quinpirole maintained its ability to reduce DOPAC but acquired that of reducing DA. Moreover, raclopride and quinpirole, when locally perfused into the mPFC of rats subjected to noradrenergic denervation, were able to increase and decrease, respectively, extracellular DA levels, while being ineffective in control rats. Transient inactivation of noradrenergic neurons by clonidine infusion into the locus coeruleus, a condition where NET is preserved, was found to reduce extracellular NE and DA in the mPFC, whereas noradrenergic denervation, a condition where NET is eliminated, almost totally depleted extracellular NE but increased DA. Both transient inactivation and denervation of noradrenergic neurons were found to reduce the number of spontaneously active DA neurons and their bursting activity in the VTA. The results indicate that DA released in the mPFC by dopaminergic terminals is not detected by microdialysis unless DA clearance from extracellular space is inactivated. They support the hypothesis that noradrenergic terminals are the main source of DA measured by microdialysis in the mPFC during physiologically relevant activities.